ANALISIS TINGKAT KESEHATAN DALAM PERSPEKTIF RASIO CAMELS (STUDI KASUS BANK SYARIAH MANDIRI PERIODE 2017-2019) - Muttaqin, Muh Syaukin; Siti Rumilah; Sindy Marchelia Putri (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2021)
Banks in a country have an important role. One of its functions is as a financial intermediary whose operations are for the community. The health of the bank and its stability is very important because it affects the ups and downs of an economy. And can foster public trust because people are more selective in choosing financial institutions. Bank Syariah Mandiri is a bank with the highest total assets compared to other Islamic banks. The purpose of this study is to find out how the level of health at Bank Syariah Mandiri during the 2017-2019 period using the CAMELS ratio. The results show that the health of Bank Syariah Mandiri Syariah, although it has a larger total asset than other Islamic banks, is still not in the very healthy category because from the research results, Bank Mandiri Syariah is currently in the healthy category. However, in the assessment of Bank Mandiri Syariah's sensitivity risk, it is in the very healthy category.